2021
DOI: 10.1371/journal.pone.0260932
|View full text |Cite
|
Sign up to set email alerts
|

Social incentive factors in interventions promoting sustainable behaviors: A meta-analysis

Abstract: Based on a meta-analysis, this paper highlights the strength and relevance of several social incentive factors concerning pro-environmental behaviors, including social influence, network factors (like network size, network connection and leadership), trust in others, and trust in institutions. Firstly, our results suggest that social influence is necessary for the emergence of pro-environmental behaviors. More specifically, an internal social influence (i.e., motivating people to change their perceptions and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…Moreover, other variables potentially explaining the intention to avoid flights might be further investigated. For example, the symbolic and social value of air travel could be examined as individual behavior is intertwined with and guided by social structures ( O’Connor, 2015 ; Windsor, 2018 ; Nguyen-Van et al, 2021 ). Further research could also consider people in their political actions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other variables potentially explaining the intention to avoid flights might be further investigated. For example, the symbolic and social value of air travel could be examined as individual behavior is intertwined with and guided by social structures ( O’Connor, 2015 ; Windsor, 2018 ; Nguyen-Van et al, 2021 ). Further research could also consider people in their political actions.…”
Section: Discussionmentioning
confidence: 99%
“…This influence motivates people to change their perceptions and attitudes and reveals its importance versus pro-environmental behaviors. Moreover, the trust in the government and institutions can promote respect for the policies dictated by policy makers, thus ensuring also positive behavioral changes (Nguyen- Van et al, 2021). These findings not only imply that policymakers should include social influence programs in their communication but also that entrusted scientific institutions can act as information carriers and foster environmental awareness toward eco-friendly behaviors.…”
Section: Outcome 7: An Inspiring and Engaging Oceanmentioning
confidence: 93%
“…Likewise, previous research suggested that the existence of incentives may be a motivating factor for pro-environmental engagement, specifically in terms of domestic recycling (e.g., Gibovic & Bikvalfi, 2021) and on-campus proenvironmental behaviors (e.g., Fu et al, 2018). Besides, a meta-analysis study (Nguyen-Van, 2021) indicated that institutional trust also needs to be taken into consideration for an effective implementation of pro-environmental behaviors. In particular, individuals -or undergraduates in our case -may be more willing to support pro-environmental policies and abandon their unsustainable habits if they have optimistic expectations about the future results of institutional (e.g., municipality, rectorate) policies in the long run.…”
Section: Amplifying the Impacts Of Sustainable Actions: What Should W...mentioning
confidence: 99%